Perfection of technical and tactical preparation of sportsmen of hand-to-hand fight - Serebryak V.V; Popov S.V; Kolosov Z.V (Kharkov National Pedagogical University, 2010)
Essence of innovative hike is considered to upgrading preparation of sportsmen of hand-to-hand fight. 58 sportsmen of section of hand-to-hand fight took part in research. Age of sportsmen are from 17 to 22 years. Developed and approved the most effective technical and tactical charts of construction of duel with the opponents of different styles of single combats. It is well-proven that offered approach instrumental in development of operative thought and adaptation to sparring of hand-to-hand fight.